Transitology: The revival of geographic-economic research on transition in Central and Eastern Europe - Herman Hoen (Economic and Environmental Studies (E&ES), 2013)
In this paper, 'transitology' as a new direction in political and economic science is discussed. The concept of 'transitology' was developed based on theories of economic transformation from a centrally planned economy towards a market economy. In the context of the questions what might the alleged research domain of this new discipline be, and what tools are available for applying transitology, the author addresses some issues with regard to the ontology and epistemology of social economic research on the transition in Central and Eastern Europe.
Keywords: 330; transitology; socio-economic transitions; Central and Eastern Europe; communist; market economy